THE SLANG WORDS IN JAY-Z’S SONG LYRICS - Junita Rahmawati; THE SLANG WORDS IN JAY-Z’S SONG LYRICS (State University of Medan, 2015)
The study deals with the Slang wordsbased on David Burke theory. Burkedividedslang wordsinto four type. There were various slang, abbreviate words,slang that is used in American television program, and the particular phrase andidoms. The objectives of this research were to find out the types of slang wordsthat is used in Jay-Z’s song lyrics and to describe the dominant one type of slangwords. This research was conducted by using descriptive qualitative method Thesources of the data were taken fom Jay-Z’s album Unfinished Business. and thedata were 7 lyrics of Jay-Z’s song lyrics. After analyzing, it was found that therewere 107 slang words in Jay-Z’s song lyrics. The findings of this research werefound that various slang 4 (3.74%), abbreviate words 73 (68.22%), slang that isused in American television program 27 (25.23%) and the particular phrase andidiom 3 (2.81%). Abbreviate words73 (68.22%) become the dominant type ofslang words in Jay-z’s song lyrics.